EFFECT OF SOIL COMPOSITION ON THE VIABILITY OF TURNIP MOTH (AGROTIS SEGETUM) PUPAE AND THE BUTTERFLY EMERGENCE RATE (Scientific journal of the Fergana State University, 2025)
This paper investigates how the physico-chemical properties of soil—including moisture level, salinity, texture, and pupal burial depth—influence the emergence of turnip moth butterflies. During the experiments, pupae (particularly in the pronymphal stage) were placed at varying depths (5, 10, 15, and 20 cm) in two different soil types from the Oltiariq and Toshloq regions. Their viability, wing integrity, and ability to fly were assessed. The results demonstrated that deeper burial, higher salinity, and insufficient moisture significantly reduce successful emergence rates, whereas optimal moisture levels and shallower burial depths facilitate more effective metamorphosis. These findings are of practical importance for improving agroecosystem management and preserving biodiversity.